x | x | π | x | |||||
cos ( | ) = sin(90 − | ) = sin( | − | ) | ||||
2 | 2 | 2 | 2 |
x | π | x | ||||
sin | + sin( | − | ) = √2sin x | |||
2 | 2 | 2 |
π |
| ||||||||||||
2sin | cos | = √2sin x | |||||||||||
4 | 2 |
π | 2x − π | |||
2 sin | cos | = √2sin x | ||
4 | 4 |
√2 | ||
sin π/4 = | ||
2 |
√2 | 2x − π | |||
2 * | cos | =√2sin x ///: √2 | ||
2 | 4 |
2x − π | ||
cos | = sin x | |
4 |
2x − π | π | |||
cos | = cos( | − x) | ||
4 | 2 |
2x − π | π | 2x − π | π | ||||
= ( | − x) lub | = 2π − | + x | ||||
4 | 2 | 4 | 2 |
x | x | x | x | |||||
sin2 | +cos2 | + 2sin | cos | = 2sin2x | ||||
2 | 2 | x | 2 |
1 | ||
2(sinx−1)(sinx+ | ) = 0 | |
2 |
x | x | x | π | |||||
sin | + cos | = √2sin( | + | ) − znana tożsamość | ||||
2 | 2 | 2 | 4 |
x | π | |||
√2sin( | + | ) = √2sinx | ||
2 | 4 |
x | π | |||
sin( | + | ) = sinx | ||
2 | 4 |
x | x | |||
sin( | ) + cos( | ) = √2sin(x) | ||
2 | 2 |
1 | x | 1 | x | ||||
sin( | ) + | cos( | ) = sin(x) | ||||
√2 | 2 | √2 | 2 |
x | π | |||
sin( | + | ) = sin(x) | ||
2 | 4 |
x | π | x | π | |||||
x = | + | + k • 2π ∨ x = π − | − | + k • 2π | ||||
2 | 4 | 2 | 4 |
π | 3 | 4 | ||||
x = | + k • 4π ∨ x = | π + k • | π | |||
2 | 2 | 3 |